Acute and Lethal Dose Toxicity Test of Pure Eel Fish (Anguilla marmorata [Q.] Gaimard) Oil in Mice (Mus musculus) - Jamaluddin Jamaluddin; Ihwan Ihwan; Khildah Khaerati; Asriani Hasanuddin; Novalina Serdiati; Jusri Nilawati; Berniawan Wijaya; Yuliet Yuliet; Iftitah Ahmad (Journal of Public Health and Pharmacy, 2025)
Introduction: Eel fish oil (Anguilla marmorata (Q.) Gaimard) highlighted its nutritional advantages, especially vitamin A, EPA (eicosapentaenoic acid), DHA (docosahexaenoic acid), and omega-3. Unsaturated fats in fish oil are known to have positive effects in the treatment of various diseases, although the potential negative impacts also need to be considered. Methods: This research aims to focus on the cytotoxic activity of eel fish oil and carry out extraction using the soxhlation method, Thomson and Weil, and Metode fixed dose. To evaluate the toxicity of the extract, the acute toxicity test was carried out by measuring the middle lethal dose (LD50), which is often used as a benchmark. Apart from that, the research also aims to determine the lethal dose 50 (LD??) value of eel fish oil, namely the dose that can cause the death of 50% of the test animal population. The extraction process uses diethyl ether solvent at 60°C, followed by purification using a 3% bentonite adsorbent. The test was carried out twice with female mice and rats as test animals, divided into groups with oral doses of 5, 50, 300, 2000, and 5000 mg/kg. Result: The results showed no deaths in the test animals, and the LD50 of eel fish oil extract was greater than the dose used. Clinical symptoms in mice include decreased motor activity and increased grooming frequency as the dose increases, as well as increased muscle tone and tension responses. Conclusion: Based on the research results, it can be concluded that eel fish oil extracts up to a dose of 5000 mg/kg are still classified as "safe" for use because they do not cause death in test animals.